Investigating the Effect of Seasonal Variation on Road Traffic Accident Occurance Along Selected Routes in Western Uganda. - Kwesiga, Ivan (Kabale University, 2024)
The study examined the seasonal variations in Road Traffic Accidents (RTAs) along Kabale Katuna, Kabale-Kisoro and Kabale Mbarara highway, western region, Uganda from 2018 to 2022 and explored the relationship between RTAs and seasonal changes and the effect of seasonal changes and road traffic accident on accident causalities on the routes. Secondary data on RTAs and mean monthly rainfall were collected for the period covered by the study from the Uganda Traffic Police Force and the Uganda National Meteorological Authority, Kabale Meteorological Station. The Analysis of Variance (ANOVA), and simple statistical techniques of frequencies and percentages were used for the data analysis. Correlation models were also used to explain variations in RTAs and to assess the degree to which the variations in RTAs were associated with the monthly rainfall. The study found out that there were 109 minor, 178 serious and 42 fatal accidents in the dry season and 121minor, 152 serious and 47 fatal accidents in wet season for the study period of 2018-2022 The study also revealed an increase of 0.77% of total traffic accidents during the Dry season. The number of RTAs and road injuries during the study period increased by 2.47% (n=133 to 149) and 4.12% respectively while death due to RTAs increased by 4.65% (n=23 to 29) from 2018 to 2022 and further revealed an increase of 0.77% of traffic accidents during the Dry season for the study period. Weak negative correlation (-0.049, -0.18 and -0.275) for the Wet season in 2021,2022 and (-0.275) for dry season of 2019 respectively, correlation between rainfall and accidents along the route during the study period is generally negative in wet season and positive in dry season. These indicate that weather is also a factor contributing to the recorded RTAs in the study area. However, the month of December and January had a highest number of registered road accidents which was associated with the higher volume of road traffic as people tend to travel more. It was concluded that there is no positive relationship between rainfall and Road traffic Accident but rather rainfall has a slight static significant on Accident Causalities due to weather changes and reduction of sight distance.